Growth and solar energy conversion in Azolla spp. grown under four solar radiation levels - de Carvalho, Edson Ferreira; Lopes, Nei Fernandes (Pesquisa Agropecuaria Brasileira, 1994)
Growth and efficiency of solar energy conversion were studied in three Azolla species (A. carofniana, A. microphylla and A. pinnata) grown under four levels (30, 50, 70 and 100%) of solar radiation incidence under outdoor conditions. Under full sunlight, A. microphylla showed higher crop growth rate, relative growth rate, net assimilation rate and efficiency of solar energy conversion than A. carofniana, A. pinnata exhibited minimal values of these growth characteristics under full exposure and maximal values at 50% of sunlight.